The deforestation story: testing for anthropogenic origins of Africa's flammable grassy biomes - Bond, William (Philos Trans R Soc Lond B Biol Sci, 2016)
Africa has the most extensive C4 grassy biomes of any continent. They are highly flammable accounting for greater than 70% of the world's burnt area. Much of Africa's savannas and grasslands occur in climates warm enough and wet enough to support closed forests. The combination of open grassy systems and the frequent fires they support have long been interpreted as anthropogenic artefacts caused by humans igniting frequent fires. True grasslands, it was believed, would be restricted to climates too dry or too cold to support closed woody vegetation. The idea that higher-rainfall savannas are anthropogenic and that fires are of human origin has led to initiatives to ‘reforest’ Africa's open grassy systems paid for by carbon credits under the assumption that the net effect of converting these system to forests would sequester carbon, reduce greenhouse gases and mitigate global warming. This paper reviews evidence for the antiquity of African grassy ecosystems and for the fires that they sustain. Africa's grassy biomes and the fires that maintain them are ancient and there is no support for the idea that humans caused large-scale deforestation. Indicators of old-growth grasslands are described. These can help distinguish secondary grasslands suitable for reforestation from ancient grasslands that should not be afforested. This article is part of the themed issue ‘The interaction of fire and mankind’.